PENGEMBANGAN ELECTRONIC PAYMENT BERBASIS ANDROID STUDI KASUS PT ABC - Mantik, Hari (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2024)
Electronic payments, or now more towards cashless and contactless methods, is a phenomenon that we can no longer avoid. For society, this has become a digital behavior that prioritizes efficiency and effectiveness, while for market players it is a strategy in facing a world based on technology, digital and science. If we quote the Bank Indonesia report which states that the value of digital banking transactions until January 2024 was recorded at 5,000 trillion, or grew 17.2% year on year, then it can be confirmed or predicted that transaction projections in the following year will experience a significant increase. Therefore, the implementation of renewable digital devices by business people is not an option, but a necessity. This journal explores a sample of Android-based EDC implementation at PT ABC to look further at the System Life Cycle process implemented in responding to demands from the market and consumers.Â Keywords: Android, Digital Wallet, Electronic Data Capture